THE UNCOUTH AND THE PUGNACIOUS IN THE TARIQAH MOVEMENTS IN NIGERIA: A LOOK AT THE IMPORTANCE OF LEARNING IN SUFISM - Dr. Musa Yusuf Owoyemi (Journal of Islamic, Social, Economics and Development, 2017)
This paper explores the issue of manner/ethics (Adab) and the importance of learning in Sufism. With a focus on the work â€œThe Spirit of Decencyâ€ (Ruhul Adab) by the Tijaniyyah master Sheikh Ibrahim Abdullah Niyass, the paper examines the centrality of the idea of ethics (Adab) in Sufism and how this helps the adherent to attain to Marifatullah (Knowledge of Allah). Going by this assertion, the paper submits that the uncouth and the pugnacious both of which seem to be the order of the day among those who practice Sufism in the contemporary time in Nigeria, are nothing but an antithesis of everything that Sufism stands for and are therefore alien to the spirit of Sufism. The paper starts by explaining the problem of the uncouth and the pugnacious in the Tariqah movements in Nigeria. It then explains the origin of Sufism by quoting the Quran and Hadith which serves as the basis of Sufism in Islam. Likewise, it examines the role of Sufism as it relates to building the manner/ethics (Adab) of an individual as well as explains the steps which a saleek/murid needs to pass through in order to obtain the knowledge of Allah (Marifatulah) and become His friend (Awliyahi Allah) â€“ which is at the heart of Sufism and its essence. The paper concludes on the note that while the uncouth and the pugnacious are alien to Sufism, learning and good manner are at the heart of it